2020
DOI: 10.1253/circj.cj-19-1199
|View full text |Cite
|
Sign up to set email alerts
|

Poor Increase in Pulse Pressure During Cardiopulmonary Exercise Testing Predicts Cardiovascular Death of Patients With Heart Failure With Reduced Ejection Fraction

Abstract: Background:The increase in stroke volume during inotropic stimulation in patients with heart failure with reduced ejection fraction (HFrEF) is called the "pump function reserve." Few studies have reported on the relationship between pump function reserve and HF prognosis. In HFrEF patients who have pump function reserve, stroke volume increases during exercise. Simply put, the pulse pressure change (∆PP) during cardiopulmonary exercise testing (CPX) is closely related to the prognosis of patients with HFrEF. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Nadruz et al [5] showed that peakVO 2 and the VE/VCO 2 slop can provide prognostic value for patients with HF; another study has shown that PETCO 2 has a greater prognostic ability than peakVO 2 for adverse events in patients undergoing cardiac resynchronization therapy (CRT) [6]. Moreover, Nakade et al [7] showed that pulse pressure differences in exercise tests can accurately predict cardiovascular death in patients with HF. In addition, the trajectory of oxygen uptake in an exercise test [8] and the size of the oscillatory ventilation ring [9] can predict the prognosis of patients with HF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nadruz et al [5] showed that peakVO 2 and the VE/VCO 2 slop can provide prognostic value for patients with HF; another study has shown that PETCO 2 has a greater prognostic ability than peakVO 2 for adverse events in patients undergoing cardiac resynchronization therapy (CRT) [6]. Moreover, Nakade et al [7] showed that pulse pressure differences in exercise tests can accurately predict cardiovascular death in patients with HF. In addition, the trajectory of oxygen uptake in an exercise test [8] and the size of the oscillatory ventilation ring [9] can predict the prognosis of patients with HF.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aimed to observe and analyze the predictive ability of CPET parameters for the re-AMI rate, incidence of HF after AMI, and death in patients with AMI after PCI to provide a reference for the postoperative management and rehabilitation of patients with AMI. Overall, this study included 375 patients who met the inclusion criteria, with an average follow-up duration of 5 years (2,7). The modeling data were divided into 269 patients in the no-event group and 41 patients in the event group, including seven patients with re-AMI complicated with HF, 13 patients with re-AMI, 18 patients with HF, and three deaths (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Nadruz et al 5 showed that peak oxygen uptake (peakVO 2 ) and the carbon dioxide ventilation equivalent slope (VE/VCO 2 slop) can provide prognostic value for patients with HF; another study has shown that peak end-tidal carbon dioxide partial pressure (PETCO 2 ) has a greater prognostic ability than peakVO 2 for adverse events in patients undergoing cardiac resynchronization therapy (CRT) 6 . Moreover, Nakade et al 7 showed that pulse pressure differences in exercise tests can accurately predict cardiovascular death in patients with HF. In addition, the trajectory of oxygen uptake in an exercise test 8 and the size of the oscillatory ventilation ring 9 can predict the prognosis of patients with HF.…”
Section: Introductionmentioning
confidence: 99%